THE CRITICAL ROLE OF EARLY DIAGNOSIS IN EHLERS-DANLOS SYNDROME: A COMPREHENSIVE REVIEW - Patrycja Rzeźnik; Barbara Wołoszyn; Maciej Sobczyk; Weronika Stachera; Julia Guzowska; Aleksandra Chajnowska; Aleksandra Borowy; Wiktoria Suchcicka; Małgorzata Zach; Julia Stępień (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Ehlers- Danlos syndrome (EDS) is a group of genetic connective tissue disorders with 13 distinguished subtypes. Approximately, 1 in 5000 people receive a diagnosis; however, this number is likely underestimated due to frequent misdiagnosis and delayed identification. The aim of this literature review is to provide a comprehensive overview of EDS, with focus on diagnostic process, common comorbidities and consequences of delayed diagnosis. State of knowledge: Among the 13 recognized EDS subtypes hypermobile EDS (hEDS), classical EDS (cEDS), and vascular EDS (vEDS) are the most prevalent. Most subtypes can be confirmed through genetic testing, however hEDS lacks a known genetic marker and is diagnosed solely on clinical criteria. This prolongs the diagnostic process-frequently exceeding a decade- leading to psychological distress and increased risk of complications in surgery or pregnancy. Comorbidities such as POTS, MCAS, and gastrointestinal dysmotility are prevalent and further complicate clinical management. Conclusion: Early detection and accurate diagnosis are crucial for improving patient outcomes and quality of life. It reduces the risk of complications, enables tailored treatment plans and helps with psychological distress of medical uncertainty. Healthcare professionals must have higher awareness about EDS in order to provide integrated, comprehensive care.